Infection by Epstein-Barr virus in Fes (Morocco). Prevalence and predictors of positivity in nasopharyngeal cancer - Mehdi El-; Rodrigo Jiménez-García; Rafael Linares-; María A. Palomar-Gallego; Isabel Jiménez-Trujillo; Ana López-; Luis Vázquez-Vázquez (Elsevier, 2018)
Objectives: To determine the prevalence and genotypic distribution of Epstein-Barr virus (EBV) in a sample of patients of Hassan II University Hospital (Morocco) due to nasopharyngeal pathologies and requiring a biopsy. We identified factors associated to the EBV infection. Methods: 112 patients were recruited (January 2012-October 2014). Biopsies were conducted for the molecular diagnosis of EBV. The data collected included sociodemographic characteristics, smoking and drug abuse, medical background and histologic diagnosis. The EBV diagnosis was performed via the Polymerase Chain Reaction. Results: 50% of patients were infected by EBV (98.2% with EBV type A compared to 1.8% type B). Most infected patients were ≥40 years(65.5%), male (59.6%) and in unfavorable socioeconomic circumstances. 83.3% of patients with lymphoma and 69.8% of patients with nasopharyngeal carcinoma presented concomitant EBV infections. 88.9% of patients who took drugs were infected by EBV compared to 47.7% of those who did not. In the multivariate analysis, age (OR 1.03; IC95% 1.02-1.06), smoking (OR 4.28; IC95%1.24-14.78) and having a malignant process (OR 6.96; IC95% 2.26-21.44) were significantly associated with EBV. Conclusions: Infection by EBV is related to several factors, such as advanced age, smoking, and suffering a malignant process. In subjects with malignant pathologies, positivity to EBV seems to be inferior to that found in other countries. Keywords: Epstein-Barr virus, Epidemiology, Outcomes, Carcinoma